Answer:
The length of AB is
units
Explanation:
The rule of the distance between two points (x1, y1) and (x2, y2) is
∵ The endpoints of AB are (-4, 5) and (2, -7)
→ Let point (-4, 5) be (x1, y1) and point (2, -7) be (x2, y2)
∴ x1 = -4 and y1 = 5
∴ x2 = 2 and y2 = -7
→ Substitute them in the rule above to find the length of AB
∵
![AB=\sqrt{(2--4)^(2)+(-7-5)^(2) }=\sqrt{(2+4)^(2)+(-12)^(2)}](https://img.qammunity.org/2021/formulas/mathematics/high-school/v5tyuitapdacrkbttjwjgff2a0ao23z3vn.png)
∴
![AB=\sqrt{(6)^(2)+144}=√(36+144)](https://img.qammunity.org/2021/formulas/mathematics/high-school/fntdyprvnm7rbe7u40cdixozjdwv1o02b5.png)
∴
![AB=√(180)=6√(5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/zuafhxr1lj5o3pw3dl6mphdzepti0mtiwn.png)
∴ The length of AB is
units